Phylogenetic analysis on family chiroptera using cytochrome B gene sequences. - Muhammad Afifi Rahim (2017)
There are about 1,240 species of Chiroptera that have been divided into two suborders: the less specialized and largely fruit-eating megabats, or flying foxes, and the highly specialized and echolocating microbats. DNA sequences of 23 species subfamily Vespertilioninae of Chiroptera that used mitochondrial cytochrome b gene to evaluate phylogenetic relationships between genera was obtained from GenBank NCBI database and were successfully aligned. The analysis of phylogeny to obtain the confidency value of each model and to compare the differences between phylogenetic methods in estimating ancestry of samples of each model involved the method of Neighbor-Joining, Minimum Evolution, Maximum Parsimony, Maximum Likelihood and Bayesian Inference. All 63 partial cytochrome b sequence fragments with at least 1,000 bp linear DNA were run through five different methods of phylogeny analysis methods. Phylogeny tree were successfully constructed for each model and were summarised accordingly with its bootstrap value.